Response of carbon fiber reinforced polymers strengthened beams to elevated temperature - Abou Ali, Reem Gamal (AUC Knowledge Fountain, 2016)
The use of carbon fiber reinforced polymers (CFRP) into the repair and retrofitting of concrete structures has been growing exponentially over the past two decades worldwide. The composite offers a superior strength- to- weight ratio as well as good durability in various service environments. The proper implementation of CFRP system involves a clean concrete surface, a powerful adhesive, such as epoxy resins together with compatible CFRP. However, one of the limiting factors towards the widespread of CFRP systems is attributed to its low resistance to elevated temperature and fire. Hence, efforts have been exerted to better understand and quantify this negative effect and to provide external protection for the system in order to alleviate the negative of impact of elevated temperature. This study focuses on assessing the impact of elevated temperature on the flexural strength of externally bonded CFRP with and without protection. Two sets of plain concrete beams have been prepared without protection and with a ready-to-use cementitious protective. All beams were subjected to temperature degrees of 70, 120 and 180 °C for 1, 2, 4 and 8 hours in a furnace. The flexural strength and mode of failure have been assessed for each set. The results of this work demonstrate the CFRP strengthened beams experienced a drastic loss in strength upon exposure to elevated temperature. The extent of the drop in strength varied according to degree of exposure as well as duration. On the whole, CFRP unprotected beams were able to restore 40% of the flexural strength at 70 °C, while the CFRP strengthened protected beams restored 20% of the flexural strength of the CFRP strengthened beams. At exposure of 120 °C the CFRP strengthened beams showed increase in the flexural strength of 40% over unstrengthened unprotected beams. The CFRP strengthened protected beams surpassed the flexural strength of the CFRP strengthened beams at 120 °C by 20%. At exposure of 180 °C, the CFRP strengthened protected and unprotected beams failed to restore the lost flexural strength for the four and eight hours of exposure. This was followed by the appearance of the normal flexural crack on all the beams. Yet, the separation of the CFRP laminates from the concrete surface were noticed only at exposure to temperatures of 120 and 180 °C. The preliminary cost of the CFRP strengthened unprotected was estimated as 90% higher than the unstrengthened unprotected beams and the CFRP strengthened protected assessed as 16% higher than the CFRP strengthened unprotected. The results unveiled the ability of the CFRP strengthened beams to enhance the flexural strength upon exposure to elevated temperature along with the ability of the fire protection system to further improve this strength. Future work should be resumed to investigate wider sets of composites, various temperatures schemes, long term properties as well as applying the system to steel reinforced beams. It is also recommended to investigate the cooling effect on the performance of the strengthened and protected beams